Comprehensive Analysis of Blood Transfusion in Paediatrics Patients admitted at Dhiraj Hospital (Medico Legal Update, 2021)
Back Ground:- Audit of transfusion practices in pediatric patients was performed to study indications ,clinical profile and whether transfusions were in accordance to guidelines.Objective:- to perform audit of transfusion practices , in order to study appropriate and inappropriate usageof different blood components in pediatric population.Results:- In present study it was observed that out of 62 packed red cells transfusions 35(56.45%) transfusionswere found to be inappropriate. Among FFP transfusions out of 55 transfusions 11(20%) transfusions wereobserved as inappropriate . Most of inappropriate transfusions had bleeds but normal coagulogram.Among Platelet transfusions , three (16.6%) platelet transfusions, out of 18 transfusions were inappropriateand transfused mainly to raise the platelet count.Conclusion:-Most frequently transfused blood components are red cells in pediatrics . Inappropriatetransfusion of blood components hinders the utility of this valuable resource , Thus it becomes necessary toconduct regular audit of blood component transfusion for optimum utilization.